Characterizaton of red fruit (Pandanus conoideus Lam) oil - Abdul Rohman,; Riyanto, Sugeng; Che Man, Yaakob (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
The present study was carried out to characterize red fruit (Pandanus conoideus Lam) oil (RFO) in term of FTIR spectra, fatty acid composition, and volatile compounds. FTIR spectrum of RFO was slightly different from other common vegetable oils and animal fats, in which in the frequency range of 1750 - 1700 cm -1, RFO appear two bands. The main fatty acid composition of RFO is oleic acid accounting for 68.80% followed by linoleic acid with the concentration of 8.49%. The main volatile compounds of RFO as determined using gas chromatography coupled with mass spectrometry (GC-MS) and headspace analyser are 1,3-dimethylbenzene (27.46%), N-glycyl-L-alanine (17.36%), trichloromethane (15.22%), and ethane (11.43%).